1985
DOI: 10.1530/acta.0.1100572
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic binding studies with [3H]oestradiol and [3H]dihydrotestosterone in the autonomic genital ganglion (plexus of Frankenhäuser) of the mouse

Abstract: Abstract. Male, female and Tfm mice (testicular feminization) were injected with [3H]oestradiol or [3H]dihydrotestosterone, and autoradiograms prepared of male accessory sex organs and of the cervico-vaginal portion of the female reproductive tract. After injection of [3H]oestradiol in male, female and Tfm animals a nuclear concentration of radioactivity was found in a subpopulation – about 20–30% – of the neurons of the genital ganglion. No such concentration was seen after [3H]dihydrotestosterone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…For example, Coujard (1951) has shown that ovariectomy decreases the volume of PG neurons and that subsequent estrogen treatment is restorative. According to Schleicher et al (1985), about 25% of mouse PG neurons bind estradiol. Since ER-α/-β localization is clearly nuclear, this suggests that estrogens have genomic effects in these neurons by hormone ligand-receptor complex binding to an estrogen response element of the DNA and modulate transcription of target genes (Murdoch and Gorski 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Coujard (1951) has shown that ovariectomy decreases the volume of PG neurons and that subsequent estrogen treatment is restorative. According to Schleicher et al (1985), about 25% of mouse PG neurons bind estradiol. Since ER-α/-β localization is clearly nuclear, this suggests that estrogens have genomic effects in these neurons by hormone ligand-receptor complex binding to an estrogen response element of the DNA and modulate transcription of target genes (Murdoch and Gorski 1991).…”
Section: Discussionmentioning
confidence: 99%